Cover Feature: A One‐Pot "Triple‐C" Multicyclization Methodology for the Synthesis of Highly Constrained Isomerically Pure Tetracyclic Peptides (ChemBioChem 18/2018). (11th September 2018) - Richelle, Gaston J. J.; Schmidt, Marcel; Ippel, Hans; Hackeng, Tilman M.; van Maarseveen, Jan H.; Nuijens, Timo; Timmerman, Peter
Abstract : The cover feature picture shows the combination of CEPS, CLIPS and CuAAC (Triple‐C) that enables the efficient one‐pot synthesis of isomerically pure tetracyclic peptides. The use of this Triple‐C methodology allowed the synthesis of mono‐ and bifunctional tetracycles, based on previously reported bicyclic leads, which showed good inhibitory activities against both uPA and FXIIa. As the icing on the cake, the 3D structure of these constructs has been unraveled by using 2D NMR analysis. More information can be found in the communication by T. Nuijens, P. Timmerman et al. onpage 1934 in Issue 18, 2018 (DOI:10.1002/cbic.201800346 ).